Sodium-dependent phosphate transporter NaPi2b as a candidate for targeted therapy: features of structure, function, and expression - R. G. Kiyamova; R. A. Vlasenkova; L. F. Bulatova (Успехи молекулярной онкологии)
The sodium-dependent phosphate transporter NaPi2b is an integral membrane protein of the SLC34 phosphate transporter family and is an attractive target for precision therapy of several human diseases. Together with other members of this family, the NaPi2b transporter is involved in maintaining phosphate homeostasis in the mammalian body. The NaPi2b transporter gene (SLC34A2) has a broad expression pattern in healthy tissues, including small intestinal epithelial cells, where NaPi2b plays a major role in the absorption of dietary phosphate. NaPi2b transports one divalentorthophosphoric acid residue into cells along with three sodium ions. NaPi2b transport is regulated by dietary phosphate, pH, hormones, and vitamins including vitamin D, estrogen, glucocorticoids, and epidermal growth factor. The NaPi2b transporter exists in two isoforms – 689 and 690 amino acid residues. The molecular weight of NaPi2b depends on the degree of glycosylation and varies from 70 to 100 kDa. According to various sources, the transporter has from 6 to 12 transmembrane domains, 2 co-transport domains, a large extracellular localization domain, as well as N- and C-terminal domains that face the inside of the cell. Impaired NaPi2b function leads to the development of several diseases, including pulmonary alveolar microlithiasis and hyperphosphatemia, and pulmonary alveolar microlithiasis is known to be associated with mutations in the SLC34A2 gene encoding NaPi2b. High levels of NaPi2b have been found in several malignant tumors, including ovary, lung, breast, thyroid, colon, bladder, liver, stomach, kidney, and in gliomas. The tumor-specific conformation of the large extracellular domain of the NaPi2b transporter, mutations, and features of expression of the transporter gene in normal and pathological conditions show that NaPi2b is a promising target for the development of highly selective targeted drugs against it for the treatment of cancer and metabolic disorders.